Basal cell carcinoma. Case presentation - Yusdenia G. Soto Serrano; Jeyffry E. García Castillo; Eduardo L. Hernández Peña; Aimeé Seife Echevarría (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Basal cell carcinoma, tumor which derives from the cells that constitute the epidermis basal layer, is the most frequent type of skin cancer and affects generally aged people. It is presented a case of a 90 year old patient, with previous history of cutaneous carcinoma on the left shoulder, presented to the opthalmology consultation complaining of volume increasing, irritation and redness in the lower eyelid of the right eye. On the physical examination it was found a lesion on the lower eyelid close the internal edge, elevated, with a diameter of 6-7 mm, ulcerated to the inside. The hist-pathological  diagnosis informed a sebaceous baso-cellular carcinoma, a differentiation of a very low frequency that motivated the presentation of this report.